Reinstating Oscar Wilde within the Literary Canon of Post Modernity: Re-visioning Salome - Dr. Mahmoud Arjoon (My University, 2012)
Oscar Wilde has always been a paradigm of opposites and contradictoriness and far beyond his literary age as far as his narratology goes. Drawing reflective sustenance from Pater and Ruskin, he moved much beyond the Victorian aesthetics into the fractured dichotomies of post-modernist functionalities and inter-texualities. Be it his first volume of poems (1881) or his first play Vera (1883) or the fairy tales (1888)or his only novel The Picture of Dorian Gray he showed a predilection for varied forms and structures disregarding the usual determinants of generic affiliation. In Salome (1893) Wilde chose to exploit a Biblical legend without dwelling on the Christian nuances and connotations and instills into the story an avant-garde and asocial viewpoint typical of his own bohemian lifestyle recasting and re-visioning the pristine tale into a modernist exposition of repressed psychological desires. The paper proposes to analyze the verbal arabesques of Salome's speeches to investigate her inexorable capacity to fly into surrealistic distortions evincing her own fractured selfhood verging on the mythically demonic, transcending the spatio-temporality of human circumstances, creating an exclusivity of being and becoming.

Oscar Wilde has always been a paradigm of opposites and contradictoriness and far beyond his literary age as far as his narratology goes. Drawing reflective sustenance from Pater and Ruskin, he moved much beyond the Victorian aesthetics into the fractured dichotomies of post-modernist functionalities and inter-texualities. Be it his first volume of poems (1881) or his first play Vera (1883) or the fairy tales (1888)or his only novel The Picture of Dorian Gray he showed a predilection for varied forms and structures disregarding the usual determinants of generic affiliation. In Salome (1893) Wilde chose to exploit a Biblical legend without dwelling on the Christian nuances and connotations and instills into the story an avant-garde and asocial viewpoint typical of his own bohemian lifestyle recasting and re-visioning the pristine tale into a modernist exposition of repressed psychological desires. The paper proposes to analyze the verbal arabesques of Salome's speeches to investigate her inexorable capacity to fly into surrealistic distortions evincing her own fractured selfhood verging on the mythically demonic, transcending the spatio-temporality of human circumstances, creating an exclusivity of being and becoming.
Reinstating Oscar Wilde within the Literary Canon of Post Modernity: Re-visioning Salome